Relative efficiency of' diammonium phosphate and Mussoorie rock phosphate in combination with crop residue incorporation on growth, yield and economics of Indian mustard (Brassica juncea) - Sharma, S N; Prasad, R; Shivay, Y S; Dwivedi, M K; Kumar, Sandeep (The Indian Journal of Agricultural Sciences, 2008)
Field experiments were conducted during 2001-04 at the Institute, New Delhi to study the effect of crop residue incorporation on the relative efficiency of di-ammonium phosphate and Mussoorie rock phosphate on Indian mustard [Brassica juncea (L.) Czernj. & Cosson]. The results indicated that phosphorus application significantly increased growth, yield parameters, yield and gross and net returns of Indian mustard. The response was limited to 40 kg P205/ha as di-ammonium phosphates while the response to Mussoorie rock phosphate was linear up to 120 kg P205/ha. Agronomic efficiency, response and economic returns at economic optimum dose with di-ammonium phosphate were higher than that of Mussoorie rock phosphate. Diammonium phosphate also gave 3-22% higher gross and 4-75% higher net returns than the Mussoorie rock phosphate. Residue incorporation had no significant effect on growth, yield attributes, yields and gross and net returns of Indian mustard but significantly increased the efficiency of Mussoorie rock phosphate.